Cytotoxic Activity of Green Seaweed Halimeda tuna Methanolic Extract Against Lung Cancer Cells - Amir Husni; Mohamad Gazali; Nurjanah Nurjanah; Rina Syafitri; Abdul Matin; Zuriat Zuriat (Pandawa Institute, 2024)
Lung cancer is a malignant tumor that attacks the lungs generated by carcinogenic free radicals such as cigarette smoke. Seaweed contains bioactive compounds that have the potential to reduce cancer-causing free radicals. This study aimed to determine the phytochemical content and cytotoxic activity of Halimeda tuna seaweed extract against lung cancer cells (A549). The H. tuna sample was macerated using methanol for 24 h. Cytotoxic test of H. tuna crude extract used the MTT test against A549. The crude extract was phytochemically tested and analyzed using gas chromatography–mass spectrometry (GC-MS). The results showed that the H. tuna crude extract had cytotoxic activity against A549 with an IC50 value of 2771 µg/mL. The phytochemical test showed that H. tuna crude extract contained flavonoids and steroids. showed the presence of fatty acid compounds including palmitic acid, oleic acid, myristic acid, palmitoleic acid and stearic acid. Based on the results can be concluded that H. tuna extract had cytotoxic activity against A549 with low cytotoxicity to be used as a chemo-preventive agent.